Target value for the maximum run-up speed of the long jump based on the performance level - Koyama, H.; Muraki, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study sought to obtain target values for the maximum run-up speed of the long jump based on performance level and to propose a method to easily estimate the maximum run-up speed. Run-up speeds of 429 male and 536 female long jumps were collected by a laser beam apparatus at 50 or 100 Hz. Subjects were divided into record-based groups for each 20 cm of the jumping distance, and the data were averaged in each group. Main results were as follows: 1) Average of maximum speed in higher performance groups was larger than that for lower groups: 2) A significantly negative correlation was observed between the interval time of the last 20 m before the takeoff and the maximum speed, and the obtained good fit regression line between them (R2=0.968) will enable to estimate and evaluate jumpers' maximum run-up speed.